Respiratory Syncytial Virus Surveillance System in Japan: Assessment of Recent Trends, 2008–2015 - Kanou, Kazuhiko; Arima, Yuzo; Kinoshita, Hitomi; Ito, Hiroaki; Okuno, Hideo; Saito, Naruo; Sunagawa, Tomimasa; Kimura, Hirokazu; Matsui, Tamano; Oishi, Kazunori (Japanese Journal of Infectious Diseases, 2018)
Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract illness in infants and young children. In Japan, surveillance for RSV infection started in 2003 based on approximately 3,000 pediatric sentinel sites. In recent years, RSV notifications have increased, but the interpretation of trends has been challenging due to a suspected increase in testing frequency and the expansion of the insurance coverage for RSV testing to include certain outpatients in late 2011. Therefore, we evaluated RSV surveillance data during 2008–2015, considering the number of sites that reported at least one RSV case during a surveillance year and restricting to sites that had continuous reporting status since 2008. While annual RSV notifications had increased, the number of sites reporting also increased. And the same magnitude of increase was not observed when the number of cases reported was restricted to the 1,372 sites that had continuous reporting status since 2008. Additionally, in the year following the insurance expansion, RSV notifications increased more remarkably for clinics than for hospitals. These results suggested that some of the recent increases in notifications might be due to an increase in testing frequency.